MULTIVARIATE ANALYSIS USE IN THE EFFICACY EVALUATION OF IMMUNOTHERAPY WITH VP-4 IN THE PATIENTS WITH BRONCHIAL ASTHMA COMPLICATED BY CHRONIC INFLAMMATION NIDI - E. M. Kostina (Acta Biomedica Scientifica, 2012)
65 patients with infection-dependent and mixed forms of bronchial asthma have been provided with immunotherapy with VP-4. With the help of multivariate analysis there have been defined the main efficacy criteria and the mathematical prediction model of the positive effect of this therapeutic method have been made.